2011
DOI: 10.1007/s12185-011-0796-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of copy number alterations by array comparative genomic hybridization in patients with late chronic or accelerated phase chronic myeloid leukemia treated with imatinib mesylate

Abstract: The outcome of treating chronic myeloid leukemia (CML) with imatinib mesylate (IM) is inferior when therapy is commenced in late chronic or accelerated phase as compared to early chronic phase. This may be attributed to additional genomic alterations that accumulate during disease progression. We sought to identify such lesions in patients showing suboptimal response to IM by performing array-CGH analysis on 39 sequential samples from 15 CML patients. Seventy-four cumulative copy number alterations (CNAs) cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…Our results in paediatric CML are also in accordance with studies performed in adults (Mullighan et al , ; Nacheva et al , ; Nadarajan et al , ; Wang et al , ). Mullighan et al used single nucleotide polymorphism arrays on 34 adult CML cases and described a mean of 0·47 CNAs per CML‐CP whereas in CML‐AP and CML‐LyBC the mean was 1·14 and 7·8, respectively (Mullighan et al , ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results in paediatric CML are also in accordance with studies performed in adults (Mullighan et al , ; Nacheva et al , ; Nadarajan et al , ; Wang et al , ). Mullighan et al used single nucleotide polymorphism arrays on 34 adult CML cases and described a mean of 0·47 CNAs per CML‐CP whereas in CML‐AP and CML‐LyBC the mean was 1·14 and 7·8, respectively (Mullighan et al , ).…”
Section: Discussionsupporting
confidence: 93%
“…In a more recent study, no IKZF1 deletions were detected in CML‐CP or CML‐AP ( N = 104) (Wang et al , ). Therefore, we conclude that clonal CNAs are rare or even absent in CML‐CP, but are relatively common at progressed stages, which is consistent with the notion that the BCR‐ABL1 fusion protein is sufficient to induce CML, but additional genomic changes are required for disease progression (Mullighan et al , ; Nacheva et al , ; Nadarajan et al , ; Wang et al , ).…”
Section: Discussionsupporting
confidence: 87%
“…SNP-a or aCGH have more recently uncovered submicroscopic regions of gain, loss, or LOH. [58][59][60][61][62][63][64][65] A summary of all such studies in CML patients is reported in Table 1. [58][59][60][61][62][63][64][65] The extreme heterogeneity of findings frustratingly suggests that high resolution fingerprinting of advanced-phase patients is unlikely to deliver (clinically) relevant information besides a more comprehensive and detailed description of the genetic 'chaos' that BP cells display (Figure 2).…”
Section: Simona Soverini Et Almentioning
confidence: 99%
“…[58][59][60][61][62][63][64][65] A summary of all such studies in CML patients is reported in Table 1. [58][59][60][61][62][63][64][65] The extreme heterogeneity of findings frustratingly suggests that high resolution fingerprinting of advanced-phase patients is unlikely to deliver (clinically) relevant information besides a more comprehensive and detailed description of the genetic 'chaos' that BP cells display (Figure 2). At the single-gene level (Table 2), the mutations/alterations classically implicated in BP include TP53 mutations (10%-30%), [66][67][68][69] RB1 mutations (up to 20% of cases), 70,71 and RUNX1 mutations 72 in BP with myeloid phenotype, and intragenic deletions of CDKN2A (50%), [73][74][75][76] and IKZF1 (65%-80%) 77,78 in BP with lymphoid phenotype.…”
Section: Simona Soverini Et Almentioning
confidence: 99%
“…Studies to date have identified DNA copy number changes that are more frequent in patients with advanced disease, suggesting that this technique could also identify molecular characteristics predictive of poor or good responses to treatment. [98][99][100] Can imatinib be discontinued in some patients?…”
Section: Improving Prognosticationmentioning
confidence: 99%